Kontribusi Sektor Pariwisata Terhadap Pendapatan Asli Daerah Kota Bukittinggi - Kevin Putra Pratama; Ariusni Ariusni; Dwirani Puspa Artha (Universitas Negeri Padang, 2023)
This study aims to analyze how big the contribution of revenue growth from the Tourism Sector to Regional Original Income (PAD) in the City of Bukittinggi, as well as to determine the development trend of the tourism sector in the City of Bukittinggi in the 2010-2030 period. This research includes descriptive and associative research with a quantitative approach using secondary data obtained from the Tourism, Youth and Sports Office and the Central Bureau of Statistics for the City of Bukittinggi. The analysis used in this research is proportionality analysis and trend analysis . The highest contribution results show in 2010 of 38% while the lowest shows in 2020 of 23%. Meanwhile, the results of forecasting the income of the tourism sector in this study show that from 2021-2030 the highest figure will be in 2030 of IDR 55,293,321,325